Tracing the evolution of STEM education: a bibliometric analysis - Abdi, Abdirahman Ibrahim; Omar, Abukar Mukhtar; Mahdi, Abdikarim Osman; Asiimwe, Constance; Osman, Mohamed Ali (Frontiers in Education, 2024)
This study presents a comprehensive bibliometric analysis of scientific research in STEM (Science, Technology, Engineering, and Mathematics) education. One thousand six hundred twenty-three studies on STEM education published between 2013 and 2023 were analyzed using bibliometric methods to uncover trends over the past decade. The analysis commenced by searching the Scopus database Core Collection for “STEM Education” publications, and bibliometric data associated with these studies was collected. The collected publications were then analyzed using VOS-viewer, a bibliometric analysis tool, to examine various bibliographic attributes. The analysis focused on key aspects such as the number of publications per year, publication types, the language of publications, year Citation Analysis, Country Collaborations, Citation Analysis (Journal, Author, Institution and Document), Co-author Analysis (Author, Countries, Institution), Co-citation Analysis (Author), and Co-occurrences Analysis. The analysis findings were visualized using VOS-viewer, a bibliometric analysis tool to depict collaboration patterns and relationships. The analysis recommends future research in STEM education to enhance interdisciplinary collaboration, address the digital divide, and integrate informal learning environments. It also underscores the importance of international collaborations, teacher professional development, and robust assessment frameworks for measuring STEM education effectiveness.